(untitled) (Journal of Economic Research & Business Administration, 2017)
The paper discusses the main directions of state support of the livestock industry in the Republic of Kazakhstan. Studied the main government programs implemented in the country in the livestock industry. Consider measures aimed at improving the competitiveness of the industry. Studied international experience of support to agriculture in developed countries (USA, Canada, UK, Germany, Australia). The analysis of the implementation of the state program “Development of export potential of cattle meat in 2011-2015”. The data on the availability of projects implemented under the program in the Akmola region. We analyzed the livestock industry of credit and subsidy processes through subsidiaries of JSC “NMH KazAgro” in 2015. The directions and the size of livestock subsidies. The necessity of state support of agricultural producers in order to increase the competitiveness of livestock production.